2004
DOI: 10.1007/s00404-003-0484-y
|View full text |Cite
|
Sign up to set email alerts
|

Reference values of ductus venosus blood flow velocities and waveform indices from 10 to 20�weeks of gestation

Abstract: Assessment of ductus venosus blood flow velocities during first and second trimester is feasible by means of color Doppler flow. The reference ranges and calculated velocities established in this study may be utilized in studies dealing with the role of ductus venosus blood flow in chromosomal abnormal fetuses, fetuses with congenital heart disease or fetal myocardial insufficiency of hypoxic origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
4
5
0
Order By: Relevance
“…Our findings were in close relation with Axt-Fliedner et al's [16] findings that were characterized by a parabolic pattern; the similarity with their result was probably due to the use of the same insonation angle correction. Fig.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings were in close relation with Axt-Fliedner et al's [16] findings that were characterized by a parabolic pattern; the similarity with their result was probably due to the use of the same insonation angle correction. Fig.…”
Section: Discussionsupporting
confidence: 92%
“…In comparison to our reference DV A wave velocity curve with those published by Bahlmann et al [15], Axt-Fliedner et al [16], and Kessler et al, [17], we have demonstrated a pattern for A wave velocity with some difference in ranges. Our findings were higher than Kessler et al's [17] findings as shown in Fig.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…1 The reference value for an abnormal DV PI was 1 or greater (95th percentile for gestational age). [1][2][3] A single investigator (J.C.) experienced in fetal echocardiography performed all examinations. Medical records were reviewed for clinical information such as maternal and fetal outcomes, gestational age at the delivery, karyotype, autopsy results, and neonatal echocardiograms.…”
Section: Methodsmentioning
confidence: 99%
“…everal studies have shown the utility of color flow and Doppler sonography as a powerful diagnostic tool for the evaluation of fetal venous and intracardiac blood flow. [1][2][3] Venous Doppler flow measurements provide additional detail in the assessment of the fetal circulation, particularly in the setting of fetal growth restriction, cardiac defects, and aneuploidy. [4][5][6][7][8][9][10][11] The ductus venosus (DV) is a fetal shunt of welloxygenated blood connecting the umbilical vein with the right atrium and directing flow across the foramen ovale into the left atrium.…”
mentioning
confidence: 99%